If Kendra is 13 years old and her age is half the age of Justin, we can express this relationship with the following equation:
Kendra's age = (1/2) * Justin's age
Since Kendra is 13 years old, we can substitute her age into the equation:
13 = (1/2) * a
Where \( a \) represents Justin's age. To eliminate the fraction, you can multiply both sides of the equation by 2:
2 * 13 = a
This simplifies to:
26 = a
Thus, the equation representing Justin's age is:
\[ a = 26 \]
In terms of the original equation, you can also rearrange it to:
\[ a = 2 * 13 \]
So, the equation that represents Justin’s age in terms of Kendra’s age is:
\[ a = 2 * 13 \] or \( a = 26 \) where \( a \) is Justin's age.